Multiple Congenital Joint Contractures, Arthrogryposis Multiplex Congenita: A Case Report - Özgün Çakmak Başer; Saime Ay; Şebnem Koldaş Doğan; Deniz Evcik (Archives of Rheumatology, 2009)
Arthrogryposis multiplex congenita is a syndrome characterized by non-progressive multiple congenital joint contractures. The exact etiology of arthrogryposis is unknown. It may be due to neuropathic or muscular pathologies, connective tissue disorders, conditions limiting the uterine space, intrauterine vascular abnormalities, or maternal diseases. In the early period of the disease, establishment of the correct diagnosis is crucial for determining the prognosis and initiation of the appropriate therapy. Herein, a 69-year-old female patient initially admitted with shoulder pain and later diagnosed to have both shoulder lesion and multiple joint contractures is presented. (Turk J Rheumatol 2009; 24: 228-31)